Good Corporate Governance and Environmental Disclosure: The Moderating Role of the Sustainability Committee - Saputro, Akbar Bayu; Wahyuningrum, Indah Fajarini Sri; Cahaya, Fitra Roman (Universitas Diponegoro, 2026)
This study investigates how elements of good corporate governance (GCG) affect environmental disclosure as a manifestation of corporate environmental responsibility, with the sustainability committee examined as a moderating variable. A quantitative research design was employed using a moderated regression analysis. The study relies on secondary data obtained from 110 basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Data analysis was conducted using SPSS Statistics version 26. The findings reveal that domestic institutional investors and institutional investors from developed countries positively influence the extent of environmental disclosure. In contrast, institutional investors from developing countries, board size, and gender diversity do not demonstrate a significant effect. The sustainability committee strengthens only the relationship between board size and environmental disclosure, while it does not moderate the effects of the other governance variables. This study extends prior research on the linkage between corporate governance mechanisms and environmental reporting. The existence of a sustainability committee reflects a company’s commitment to integrating sustainability principles into its policies and operational strategies, aligning corporate activities with the Sustainable Development Goals (SDGs) through the pursuit of balanced economic, social, and environmental performance.